Anti-carcinogenic Potential of Nano-curcumin -“Killing Cancerous Cells” - Khan, Mohsin Ali; Khan, Anwar; Khan, Akhlak Ahmed; Simrah; Mirza, Mohd. Aamir; Naquvi, Kamran Javed; Kumar, Devendra (Current Bioactive Compounds, 2025)
Nowadays, cancer treatment is currently limited to surgery, chemotherapy, and radiation, which carry the risk of damaging the normal tissue of the body and incomplete removal of the cancerous cells from the body. Thus, the Nano technique offers a great means to target therapies directly on cancerous cells and neoplasm. Moreover, because nano-based formulations of polyphenolic curcumin show a major effect on cancer and tumour cells, nanoparticles have a tendency to overcome the hydrophobic nature of curcumin to improve its stability and bioavailability in vitro and in vivo. It is apparent from the studies that Curcumin has shown anticancer effects by regulating various immunomodulators, which include cytokines, reactive oxygen species, and cyclooxygenase-2 (COX-2). It also takes part in the downregulation of growth factors, protein kinases, oncogenic molecules, and various signalling pathways, such as nuclear factor kappa-light-chain enhancer of activated B cells (NF-κB), c-Jun N-terminal kinase (JNK), and signal transducer and activator of transcription 3 (STAT3) signalling. According to recent studies and clinical trials, nano curcumin shows a major effect on cancerous cells. In this article, the authors summarised the mechanism of nano curcumin in various metastatic cancers and the most recent clinical trials performed.
Keywords: curcumin